2002
DOI: 10.1063/1.1513662
|View full text |Cite
|
Sign up to set email alerts
|

High temperature stability of Al2O3 dielectrics on Si: Interfacial metal diffusion and mobility degradation

Abstract: We have examined the stability of Al2O3/Si heterostructures and show that significant Al diffusion occurs into the silicon for temperatures of 1000 °C and more. This may be caused by dissociation of small quantities of Al2O3 and subsequent dissolution of the Al into the silicon. Such diffusion may be reduced, though not eliminated via an interfacial silicon oxynitride diffusion barrier. Using long channel metal gate Al2O3/Si n field effect transistor data, we show that anneals at 1000 °C result in a degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 10 publications
1
41
1
Order By: Relevance
“…The mobility is limited mainly by interface roughness over the range of interest. The mobilities in devices with high K gate oxides presently lie well below the universal curve [6,23,32,[121][122][123][124][125]. This is particularly true of NMOS devices.…”
Section: Mobility Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…The mobility is limited mainly by interface roughness over the range of interest. The mobilities in devices with high K gate oxides presently lie well below the universal curve [6,23,32,[121][122][123][124][125]. This is particularly true of NMOS devices.…”
Section: Mobility Degradationmentioning
confidence: 99%
“…Al 2 O 3 does not have soft modes, but it does have a high defect concentration. Thus, the reduced mobility seen in those devices [122] can only arise from charge scattering. [123,131] introduced a general model including the above effects.…”
Section: Mobility Degradationmentioning
confidence: 99%
“…Secondly, though Al 2 O 3 has been predicted to be thermodynamically stable with Si, dissociation of Al 2 O 3 and subsequent dissolution of the Al into the silicon has recently been shown to occur at high RTA temperatures [14]. It was also suggested that the Al diffusion into the Si substrate causes defects in the high-j dielectric and in the Si substrate.…”
Section: Resultsmentioning
confidence: 98%
“…Studies in [2,3] showed different physical properties of ALD-Al 2 O 3 films depending on process conditions. Also the impact of Al 2 O 3 dielectric on semiconductor electrode doping was shown [4]. However, a systematic comparison of available processes and its effect on physical properties was not done so far.…”
Section: Introductionmentioning
confidence: 98%